Photocatalytic degradation of pharmaceuticals using TiO2 based nanocomposite catalyst - review - Fawzi Suleiman Khasawneh, Omar; Palaniandy, Puganeshwary (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The occurrence of contaminants of emerging concern (CECs) such as pharmaceutical compounds (PhACs) is becoming a major global issue due to the persistence, bioaccumulation, and toxicity of these pollutants. Human and animal consumption was recognized as the major sources for pharmaceutical pollution. Existent conventional treatment processes have shown low degradation efficiencies towards PhACs.
Keywords: nanocomposite; catalyst; photocatalysis; TiO2; pharmaceutical compounds; photocatalytic process; titanium dioxide; nanokompozyt; katalizator; fotokataliza; związki farmaceutyczne; proces fotokatalityczny; dwutlenek tytanu